Development of inhalable Erlotinib-Loaded Polymeric Micelles for Treatment of Non-Small Cell Lung Cancer: an in Vitro Study - Sulaiman S. Alhudaithi; Raisuddin Ali; Sarah O. Abaalola; Taghreed H. Altoum; Alhassan H. Aodah; Sarah M. Almufadhili; Nasser B. Alsaleh; Rawan Fitaihi; Ziyad Binkhathlan (Journal of Pharmaceutical Innovation, 2026)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

Whole-Blood Metabolomics of a Rat Model of Repetitive Concussion - Ahmad Raza Khan; Samiya Zehra; Atul Kumar Baranwal; Dinesh Kumar; Raisuddin Ali; Saleem Javed; Kamlesh Bhaisora (Journal of Molecular Neuroscience, 2023)

Application of green nanoemulsion to treat contaminated water (bulk aqueous solution) with azithromycin - Afzal Hussain; Obaid Afzal; Abdulmalik S.A. Altamimi; Raisuddin Ali (Environmental Science and Pollution Research, 2021)

Pharmacokinetic and Tissue Distribution of Orally Administered Cyclosporine A-Loaded poly(ethylene oxide)-block-Poly(ε-caprolactone) Micelles versus Sandimmune® in Rats - Ziyad Binkhathlan; Raisuddin Ali; Wajhul Qamar; Hanan Al-Lawati; Afsaneh Lavasanifar (Pharmaceutical Research, 2021)

Nanosuspension-Based Aloe vera Gel of Silver Sulfadiazine with Improved Wound Healing Activity - Md Abul Barkat; Harshita; Iqbal Ahmad; Raisuddin Ali; Satya Prakash Singh; Faheem Hyder Pottoo; Sarwar Beg; Farhan Jalees Ahmad (AAPS PharmSciTech, 2017)

Analysis of Trace Elements in Rat Bronchoalveolar Lavage Fluid by Inductively Coupled Plasma Mass Spectrometry - Wajhul Qamar; Abdul Rahman Al-Ghadeer; Raisuddin Ali; Hatem A. Abuelizz (Biological Trace Element Research, 2017)

Effervescence Assisted Fusion Technique to Enhance the Solubility of Drugs - Mohd Aftab Alam; Fahad I. Al-Jenoobi; Abdullah M. Al-Mohizea; Raisuddin Ali (AAPS PharmSciTech, 2015)

Heat stress‐induced alterations of antioxidants in the freshwater fish Channa punctata Bloch - M. Kaur; F. Atif; M. Ali; H. Rehman; S. Raisuddin (Journal of Fish Biology, 2005)
The effect of elevated temperature on the antioxidants in the freshwater fish Channa punctata was investigated. Fish stressed with an elevated temperature of 12° C, range ± 1° C over the ambient temperature for 3 h showed a significant ( P P P

Modulatory Effect of Cadmium Exposure on Deltamethrin-Induced Oxidative Stress in Channa punctata Bloch - F Atif; S Parvez; S Pandey; M Ali; M Kaur; H Rehman; H A Khan; S Raisuddin (Archives of Environmental Contamination and Toxicology, 2005)

Modulatory Effect of Cadmium Injection on Endosulfan-Induced Oxidative Stress in the Freshwater Fish, Channa punctata Bloch - F. Atif; M. Ali; M. Kaur; H. Rehman; S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 2005)